Kedudukan Akta Risalah Lelang Sebagai Bukti Peralihan Hak Milik Atas Tanah Bagi Warga Negara Asing - Sudiarto, Sudiarto; Kurniawan, Kurniawan; Hirsanuddin, Hirsanuddin (Fakultas Hukum Universitas Mataram, 2021)
Auction is a sale of goods which is open to the public with a written and or oral price offering which is increasing or decreasing to reach the highest price, which is preceded by an auction announcement. The legal consequence of selling by auction is that if a foreigner wins the auction, he will receive the delivery of â€œproperty rightsâ€ from the auction object in the form of an object of mortgage, while on the other hand it determines that the land law system in Indonesia adheres to the principle or principle of nationality. The meaning of the principle of nationality is that foreign citizens are not allowed to obtain ownership rights to land in Indonesia. This research uses normative legal research. The results of the discussion of this research are the status of the Minutes of auction as evidence of transfer of title to land for foreign citizens, namely the deed of auction minutes made by auction officials can be used as a basis for evidence of transfer of ownership rights to land for foreign citizens in the National Land Agency agency.